The concept of centre-periphery in the work of Daido Moriyama - Fernández, Jose Maria Gutiérrez-Cuevas (Street Art & Urban Creativity, 2016)
This text analyses the concept of centre-periphery in the work of the photographer Daido Moriyama. The objective is to study how the binomial centre-periphery becomes blurred in postmodern society. The work explores how difficult it is to distinguish centre from periphery in the postmodern era, to know where one starts and the other finishes. It’s a Japanese vision on the theme, which sees beauty in darkness and shadows, unlike the western world, where aesthetics is typically built around light.